HMGA2 is associated with the aggressiveness of tongue squamous cell carcinoma. (23rd December 2016) - Zhang, H; Tang, Z; Deng, C; He, Y; Wu, F; Liu, O; Hu, C
Abstract : Objective: To analyze the effects of HMGA2 on proliferation, invasion, and metastasis in tongue squamous cell carcinoma (TSCC). Methods: HMGA2 knockdown was performed in SCC15 cell lines, and functional assay was applied to observe the effects on cell migration and invasion. Real‐time PCR, Western blotting, and immunohistochemistry (IHC) were also used to measure the expression of HMGA2 and EMT markers. Results: HMGA2 expression was decreased after lentivirus infection. Functional assay showed that silence of HMGA2 can inhibit the proliferation of SCC15 cells and arrest the cells in G1/S phase. Moreover, knockdown of HMGA2 enhanced apoptosis of SCC15 cells. Wound‐healing assay and transwell assay indicated that knockdown of HMGA2 significantly inhibited migration and invasion ability of SCC15 cells. Expression detection suggested that HMGA2 may be involved in the metastasis of SCC15 cells by activating Twist family expression and inducing epithelial–mesenchymal transition (EMT) process. IHC analysis showed that HMGA2 and vimentin were up‐regulated in TSCC tissues, while E‐cadherin was down‐regulated. Clinicopathological analysis indicated that expression of HMGA2, E‐cadherin, and Vimentin were associated with recurrence of patients with TSCC. Conclusion: Our findings demonstrated that HMGA2 may promote malignant transformation of TSCC through EMT process and may be an independent prognosis biomarker for TSCC.